Biomass polymer-assisted fabrication of aerogels from MXenes with ultrahigh compression elasticity and pressure sensitivity. Issue 17 (4th April 2019) - Hu, Yijie; Zhuo, Hao; Luo, Qingsong; Wu, Yaxiao; Wen, Rui; Chen, Zehong; Liu, Linxiang; Zhong, Linxin; Peng, Xinwen; Sun, Runcang
Abstract : A compressible and conductive aerogel with not only super mechanical performances but also ultrahigh linear sensitivity is fabricated by connecting Ti3 C2 nanosheets into continuous and ordered lamellae using the biopolymer chitosan. Abstract : Compressible and conductive materials (CCMs) have important applications in developing pressure sensors for various wearable devices. However, it is a great challenge to fabricate a CCM with superior mechanical properties and ultrahigh linear sensitivity. Herein, we developed a green and effective method to fabricate a lightweight, compressible and conductive aerogel by connecting Ti3 C2 nanosheets into continuous and ordered lamellae with a biomass polymer (chitosan). Due to the connecting effect, the lamellae are flexible, highly compressible and elastic as well as structurally stable. These features allow the aerogel to withstand extremely high strain (99%), long-term compression (up to 150 000 cycles), and repeated bending. Furthermore, due to the unique lamellar architecture, the aerogel demonstrates an ultrahigh sensitivity (80.4 kPa −1 ) and exceptionally wide linear range (within strain of 0.5–70%). In addition, it has low detection limits for tiny strain (0.5%) and pressure (1.0 Pa). Due to these advantages, the aerogel shows potential for application in flexible wearable devices for detecting biosignals.